The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/antibiotics9040152
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Virulence Traits in Vancomycin-Resistant Enterococci (VRE) and Extended-Spectrum β-Lactamase/AmpC-producing (ESBL/AmpC) Enterobacteriaceae from Humans and Pets

Abstract: Background: We investigated the virulence factors, genes, antibiotic resistance patterns, and genotypes (VRE and ESBL/AmpC) production in Enterococci and Enterobacteriaceae strains isolated from fecal samples of humans, dogs, and cats. Methods: A total of 100 fecal samples from 50 humans, 25 dogs, and 25 cats were used in the study. MICs of nine antimicrobials were determined using the broth microdilution method. Polymerase chain reaction was used for the detection of genes responsible for antibiotic resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 66 publications
3
34
1
1
Order By: Relevance
“…Some reports have detected enterococci resistant to tetracycline and erythromycin in wild Iberian wolves, Iberian lynx, and red foxes in Portugal (43)(44)(45). Additionally, domestic canids and felids also harbored antimicrobial-resistant enterococci (47,52,53).…”
Section: Antimicrobial Susceptibility Profilementioning
confidence: 99%
“…Some reports have detected enterococci resistant to tetracycline and erythromycin in wild Iberian wolves, Iberian lynx, and red foxes in Portugal (43)(44)(45). Additionally, domestic canids and felids also harbored antimicrobial-resistant enterococci (47,52,53).…”
Section: Antimicrobial Susceptibility Profilementioning
confidence: 99%
“…Resistance to vancomycin, an important alternative to methicillin-resistant bacteria, is increasing. Despite vancomycin recording a very low resistance of up to 0% [ 196 ], recent studies showed increasing vancomycin resistance as high as 24% [ 197 ]. Moreover, antimicrobial resistance among bacterial species that are opportunistic to humans, such as Klebsiella and Acinetobacter spp., is an emerging human health concern [ 198 , 199 , 200 , 201 ].…”
Section: The Role Of Insects Rodents and Pets In Amr Persistencementioning
confidence: 99%
“…In particular, the VanA cluster provides high-level resistance to vancomycin and teicoplanin, whereas strains possessing the VanB cluster retain their susceptibility to teicoplanin [45]. In a recent study, 200 enterococcal isolates of human and animal origin were analyzed, revealing the prevalence of teicoplanin-and vancomycin-resistant strains in domestic animals, together with the co-existence of virulence traits [46].…”
Section: Antibiotic Resistance and Options For Treatmentmentioning
confidence: 99%